Modernizar la tradición. Carlos Rojas en Artesanías de Colombia durante los años 70 - María Amalia García (Centre de Recherches sur les Mondes Américains, 2017)
This paper analyzes Carlos Rojas´ work in the public-private enterprise “Artesanías de Colombia” during the 1970s. During his administration there was a modernization in the way of conceptualizing, producing and putting into circulation the handcrafts in this South American country. The hypothesis of this work argues that Rojas – an important Colombian abstract artist – went across the themes, functions, techniques and materials of rural crafts from modern art language. This art crafts process of modernization – that involves operations of synthesis and condensation of formal elements and the renewal of chromatic aspects – carried out by Rojas from “Artesanías de Colombia” sought a national and international circulation and consumption. This work does not pretend to carry out an exhaustive study of the Colombian craft. Some examples of handcrafts will be analyzed as varnish of the city of Pasto (barniz de Pasto-Department of Nariño), animals figures made from wood (Bogotá) and Tagua seed carvings (Chiquinquirá).